Апробація ГІС режиму ґрунтової вологи в умовах ДП «Дніпро» інституту зернових культур НААН України - Коваленко, Володимир Васильович; Kovalenko, Vlаdіmyr Vasiljevich; Довганенко, Денис Олександрович; Dovganenko, Denis Aleksandrovich; Ткаченко, Олександр Сергійович; Tkachenko, Alexander Sergeevich (Дніпро, 2017)
Проведена виробнича перевірка методу розрахунку вологи на дослідному полі ДП Дніпро Інституту зернових культур НААНУ. Алгоритм розрахунку волозапасів реалізовано на базі Quantum GIS як скрипт-модель. Робота є показовим свідченням необхідності симбіозу геоінформаційних технології та розрахункових методів The production verification of the moisture calculation method at the experimental field of the GP Dnepr Institute of Grain Crops of the UAAS was carried out. The algorithm for calculating hair weighers is implemented on the basis of Quantum GIS as a script-model. The work showed the need for a symbiosis of geo-information technologies and computational methods
Approval of GIS of the regime of soil moisture in conditions of SE "Dnipro" of the Institute of grain crops of the National Academy of Sciences of Ukraine
Keywords: метод розрахунку вологозапасів; method for calculating moisture reserves; виробнича перевірка; production verification; ГІС режиму запасів вологи; GIS regime of moisture reserves